Conductive substrate and method for manufacturing the same
By preparing silver-containing conductive thin wires in the conductive matrix, controlling the ratio of silver to iodine, combined with the electroplating silver plating treatment, the problems of insufficient conductivity and serious migration phenomena are solved, and the high conductivity and migration suppression effect of the conductive matrix are achieved.
Patent Information
- Application Number
- JP2023159070
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-04
AI Technical Summary
The conductive thin wires in existing conductive substrates have problems such as insufficient conductivity and serious migration in touch panel applications, resulting in the circuit function of the conductive thin wires being invalid.
By preparing silver-containing conductive thin wires in the conductive matrix, and controlling the ratio of silver to iodine between 0.035 and 0.100, combined with the electroplating silver plating treatment, a conductive matrix with excellent conductivity and migration suppression properties was formed.
The high conductivity and migration suppression effect of the conductive matrix are achieved, ensuring the stability and reliability of conductive thin wires in touch panel applications.
Smart Images

Figure 2025050341000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a conductive substrate having conductive thin wires and a method for manufacturing the conductive substrate. [Background technology]
[0002] BACKGROUND ART Conductive substrates having conductive thin wires (thin wire-like wiring exhibiting conductivity) are widely used for various applications such as touch panels. As shown in Patent Document 1, for example, the conductive thin wires of the conductive substrate are formed by sequentially carrying out exposure processing, development processing, etc. on a photosensitive layer containing silver halide to form conductive thin wires containing metallic silver.
[0003] Patent document 1 describes a method for manufacturing a conductive substrate, which includes, in order, step 1 of forming thin wires containing a metal on a substrate, step 2 of contacting the thin wires with a solution containing an organic acid, and step 3 of plating the thin wires to form conductive thin wires. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2022-161790 Summary of the Invention [Problem to be solved by the invention]
[0005] When a conductive substrate having conductive thin wires is used in, for example, a touch panel, the conductive thin wires are required to have excellent conductivity, that is, low electrical resistance. Furthermore, while there is a demand for thinner conductive wires, there is a problem in that conductive patterns formed using such thin conductive wires are more susceptible to migration. If migration occurs between the conductive thin wires, the conductive thin wires may become conductive and may not function as intended. Therefore, there is a demand for conductive substrates with improved migration suppression performance.
[0006] The present inventors have studied conductive substrates having conductive thin wires with reference to Patent Document 1 and have found that there is room for further improvement in conductive substrates that are excellent in both conductivity and migration suppression performance.
[0007] In view of the above circumstances, the present invention provides a conductive substrate that has excellent conductivity and excellent migration suppression performance, and a method for producing the conductive substrate. [Means for solving the problem]
[0008] [1] A conductive substrate comprising a substrate and a conductive thin wire containing silver arranged on the substrate, wherein the ratio of the amount of iodine atoms to the amount of silver atoms detected when the surface of the conductive thin wire is measured by fluorescent X-ray analysis is 0.035 to 0.100. [2] The conductive substrate according to [1], wherein the conductive thin wires have a line width of 0.1 μm or more and less than 5.0 μm. [3] The conductive substrate according to [1] or [2], wherein in a vertical cross section of the conductive thin wire in a direction perpendicular to the direction in which the conductive thin wire extends, the ratio of the height of the conductive thin wire to the line width of the conductive thin wire is 0.6 or more and less than 1.5. [4] The conductive substrate according to any one of [1] to [3], wherein the silver contained in the conductive thin wires is in the form of particles. [5] The conductive substrate according to any one of [1] to [4], wherein the substrate is a flexible substrate. [6] The conductive substrate according to [5], wherein the material constituting the flexible substrate is at least one selected from the group consisting of polyethylene terephthalate, cycloolefin polymer, cycloolefin copolymer, and polycarbonate. [7] A method for producing a conductive substrate, which includes a substrate and conductive thin wires containing silver arranged on the substrate, the method comprising the steps of: Step 1 forming a thin wire-shaped metal-containing layer on the substrate; and Step 2 forming the conductive thin wires by electroless plating the metal-containing layer, in this order; wherein a plating solution used in the electroless plating contains potassium iodide and a reducing agent, the content of the reducing agent in the plating solution is 60 mmol / L or less, and the contents of the potassium iodide and the reducing agent in the plating solution are each C KI mmol / L and C R When expressed as mmol / L, C KI / C R A method for manufacturing a conductive substrate that satisfies x 1000≦0.7. [8] The method for producing a conductive substrate according to [7], wherein the electroless plating treatment is electroless silver plating treatment. [Effects of the Invention]
[0009] According to the present invention, it is possible to provide a conductive substrate that has excellent conductivity and excellent migration suppression performance, and a method for producing the conductive substrate. [Brief explanation of the drawings]
[0010] [Figure 1] 1 is a schematic perspective view showing an example of the configuration of a conductive substrate of the present invention. [Figure 2] 1 is a plan view showing an example of a mesh pattern formed by conductive thin wires of a conductive substrate of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0011] The conductive substrate of the present invention will be described in detail below with reference to the drawings. The following description of the components is based on a typical embodiment of the present invention, and the present invention is not limited to such an embodiment. The drawings are merely illustrative of the present invention and are not intended to limit the scope of the present invention, and the scales of the components shown in the drawings may differ from the actual scales. In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. In this specification, each component may be a single substance corresponding to the component, or two or more substances may be used in combination. When two or more substances are used in combination for each component, the content of the component refers to the total content of the substances used in combination, unless otherwise specified. In this specification, "g" and "mg" represent "g mass" and "mg mass", respectively. As used herein, the term "polymer" or "polymer compound" refers to a compound having a weight-average molecular weight of 2000 or more. Here, the weight-average molecular weight (Mw) is defined as a polystyrene-equivalent value measured by GPC (Gel Permeation Chromatography). Furthermore, with regard to angles, "orthogonal" or "perpendicular" means a range of 90°±5°, and "parallel" means a range of 0°±5°. Similarly, unless otherwise specified, angles mean that the difference from the exact angle is within a range of 5 degrees. The difference in the above angles is preferably within 4 degrees, and more preferably within 3 degrees.
[0012] [Conductive substrate] The conductive substrate according to the present invention includes a substrate and a conductive thin wire containing silver and disposed on the substrate. FIG. 1 is a schematic perspective view showing an example of a conductive substrate according to the present invention. The conductive substrate 10 has a substrate 12 and conductive thin wires 14 containing silver that are disposed on a surface 12a of the substrate 12. Note that, although two conductive thin wires 14 extending in one direction are shown in Fig. 1, the arrangement of the conductive thin wires 14 and the number thereof are not particularly limited.
[0013] 1 is a cross section obtained by cutting the thin conductive wire 14 along a plane perpendicular to the direction DL in which the thin conductive wire 14 extends. In other words, the vertical cross section Ac of the thin conductive wire 14 includes a direction DW perpendicular to the direction DL in which the thin conductive wire 14 extends.
[0014] 〔substrate〕 The substrate is not particularly limited as long as it is a material that can support the conductive thin wires, and examples thereof include a plastic substrate, a glass substrate, and a metal substrate. The substrate is preferably flexible because the resulting conductive member has excellent bendability. Materials constituting the flexible substrate include, for example, polyethylene terephthalate (PET), cycloolefin polymer (COP), cycloolefin copolymer (COC), and polycarbonate (PC). Of these, PET is preferred because of its excellent adhesion to the conductive thin wires.
[0015] The thickness of the substrate is not particularly limited and is often 25 to 500 μm. When the conductive substrate is applied to a touch panel and the substrate surface is used as the touch surface, the thickness of the substrate may exceed 500 μm. The total light transmittance of the substrate is preferably 85 to 100%. The total light transmittance is measured according to "Plastics - Determination of total light transmittance and total light reflectance" as defined in JIS (Japanese Industrial Standards) K 7375:2008.
[0016] A primer layer may be disposed on the surface of the substrate. The undercoat layer preferably contains a specific polymer, which will be described later. Use of this undercoat layer further improves the adhesion of the conductive thin wires, which will be described later, to the substrate. The method for forming the undercoat layer is not particularly limited, and examples thereof include a method in which a composition for forming an undercoat layer containing a specific polymer described below is applied to a substrate, and heat treatment is performed as necessary. The composition for forming an undercoat layer may contain a solvent as necessary. The type of solvent is not particularly limited, and examples thereof include solvents used in the composition for forming a photosensitive layer described below. Furthermore, a latex containing particles of a specific polymer may be used as the composition for forming an undercoat layer containing a specific polymer. The thickness of the undercoat layer is not particularly limited, but is preferably 0.02 to 0.3 μm, more preferably 0.03 to 0.2 μm, in terms of better adhesion of the conductive layer to the substrate.
[0017] [Conductive thin wire] The conductive thin wires are disposed on the surface of the substrate, and the conductive thin wires contain silver, which ensures the conductive properties of the conductive substrate. The conductive thin wires being arranged on the surface of the substrate means that the conductive thin wires may be in direct contact with the surface of the substrate, or the substrate and the conductive thin wires may be arranged via another layer (for example, the above-mentioned undercoat layer).
[0018] In this specification, the term "conductive thin wires" refers to thin wire-shaped regions that are disposed on the surface of a substrate and are integrally formed of a material containing silver. For example, the silver halide-free layer formed in step E (described later) and the protective layer formed in step F (described later) constitute conductive thin wires together with the thin wire-shaped silver-containing layers formed in steps A and B (described later). Furthermore, the conductive thin wires arranged on the surface of the substrate may or may not be electrically connected to a member external to the conductive substrate, and a part of the conductive thin wires may be a dummy electrode electrically insulated from the outside.
[0019] The conductive thin wire contains silver (metallic silver). The silver contained in the conductive thin wire may be simple silver or a mixture of silver and a metal other than silver. Examples of other metals include copper (metallic copper), gold (metallic gold), nickel (metallic nickel), and palladium (metallic palladium), with copper being preferred. Hereinafter, unless otherwise specified, the term "silver" simply means "metallic silver." The thin conductive wires are preferably made of silver alone or a mixture of silver and copper, and more preferably made of silver alone, since this can prevent breakage of the thin conductive wires.
[0020] The silver contained in the conductive thin wire is usually in the form of particles. The average particle diameter of the particulate silver is preferably 10 to 1000 nm, more preferably 10 to 200 nm, in equivalent-sphere diameter. The equivalent-sphere diameter is the diameter of a spherical particle having the same volume, and the average particle diameter of silver particles is obtained by measuring the equivalent-sphere diameters of 100 objects and calculating the arithmetic mean. The shape of the silver particles is not particularly limited, and examples thereof include spherical, cubic, tabular, octahedral, and tetradecahedral shapes. In the conductive thin wire, the silver may be in a shape other than particulate, for example, fused and bonded in part or entirely, or may be dispersed in the conductive thin wire in the form of layers. The conductive thin wire may have a structure in which a plurality of silver particles are dispersed in a polymer compound, or silver particles may be aggregated in the polymer compound to exist as aggregates. Furthermore, at least some of the silver particles contained in the conductive thin wire may be bonded to each other by a silver plating process described below. The polymer compound will be described later.
[0021] <Silver content> The silver content of the conductive thin wires is not particularly limited, and in order to obtain a conductive substrate with superior conductivity, the silver content per area of the region on the substrate surface where the conductive thin wires are arranged is preferably 0.01 to 10 g / m. 2 It is preferable that the density is 0.03 to 1 g / m 2 It is more preferable that:
[0022] The silver content in the conductive thin wires can be adjusted, for example, by the content of the silver component (e.g., the silver halide contained in the composition for forming the photosensitive layer described below) contained in the composition for forming the conductive thin wires, and the amount of silver plating in the plating process described below. The silver content in the conductive thin wires can be obtained by measuring the weight of silver contained in the conductive thin wires per area of the main surface of the substrate using a fluorescent X-ray measuring device.
[0023] <Ratio of the amount of iodine atoms to the amount of silver atoms (ratio I / Ag)> In the conductive thin wire according to the present invention, the ratio of the amount of iodine atoms to the amount of silver atoms detected when the surface of the conductive thin wire is measured by fluorescent X-ray analysis (hereinafter also referred to as "ratio I / Ag" in this specification) is 0.035 to 0.100.
[0024] The conductive substrate according to the present invention has excellent conductivity and excellent migration suppression performance due to the ratio I / Ag on the surface of the conductive thin wires being 0.035 to 0.100. The details of why the conductive substrate according to the present invention exhibits the above-mentioned excellent effects are unclear, but it is speculated as follows: The presence of a certain amount or more of iodine on the surface of the conductive thin wires suppresses migration of the conductive thin wires. On the other hand, if the amount of iodine present on the surface of the conductive thin wires is too large, the conductivity of the conductive substrate decreases, and it is speculated that this is because the proportion of silver in the conductive thin wires decreases. Hereinafter, the expression "the effects of the present invention are superior" means that at least one of migration suppression performance and electrical conductivity is superior in a conductive substrate.
[0025] The method for measuring the ratio I / Ag on the surface of the conductive thin wire by fluorescent X-ray analysis will be described below. The ratio I / Ag was measured by repeating Ar sputtering (2 kV, Ar ions, 2 mm × 2 mm) from the surface of the conductive thin wire opposite the substrate toward the depth direction, and X-ray fluorescence analysis (XPS, X-ray source: Al Kα, Quantera SXM manufactured by ULVAC-PHI, Inc.). The above Ar sputtering and X-ray fluorescence analysis are repeated on a sample of the conductive substrate, and the position at a depth where the ratio of the number of metal atoms to the total number of atoms is 15% or more is defined as the surface of the conductive thin wire, and the area toward the substrate from that position is defined as the interior of the conductive thin wire. Then, X-ray fluorescence analysis is performed on the surface of the conductive thin wire, and the above ratio I / Ag (iodine atom content / silver atom content) can be calculated from the measured values of the atomic weights of silver atoms and iodine atoms obtained.
[0026] It is presumed that iodine atoms exist on the surface of the conductive thin wire as iodine-containing compounds such as silver iodide and potassium iodide.
[0027] The ratio I / Ag on the surface of the conductive thin wire is preferably 0.040 to 0.080, as this will provide better effects of the present invention. The ratio I / Ag on the surface of the conductive thin wire can be adjusted, for example, by the amount of iodine compound and reducing agent contained in the plating solution used in the electroless plating process in step W of forming the conductive thin wire by performing an electroless plating process in the method for producing a conductive substrate described below.
[0028] The conductive thin wire may contain a polymer compound in addition to silver and iodine (iodine compound). The type of polymer compound contained in the conductive thin wire is not particularly limited, and known polymer compounds can be used. Among them, polymer compounds other than gelatin (hereinafter also referred to as "specific polymers") are preferred in that they can form conductive thin wires with superior strength. The type of specific polymer is not particularly limited as long as it is different from gelatin, and a polymer that is not decomposed by proteolytic enzymes or oxidizing agents that decompose gelatin, which will be described later, is preferred. Examples of the specific polymer include hydrophobic polymers (water-insoluble polymers), such as at least one resin selected from the group consisting of (meth)acrylic resins, styrene resins, vinyl resins, polyolefin resins, polyester resins, polyurethane resins, polyamide resins, polycarbonate resins, polydiene resins, epoxy resins, silicone resins, cellulose polymers, and chitosan polymers, or copolymers of monomers constituting these resins. The specific polymer preferably has a reactive group that reacts with a crosslinking agent, which will be described later. The specific polymer is preferably in the form of particles, that is, the conductive thin wire preferably contains particles of the specific polymer.
[0029] The specific polymer is preferably a polymer (copolymer) represented by the following general formula (1). General formula (1): -(A) x -(B) y -(C) z -(D) w - In the general formula (1), A, B, C, and D represent repeating units represented by the following general formulae (A) to (D), respectively.
[0030] [ka]
[0031] R 11 represents a methyl group or a halogen atom, and is preferably a methyl group, a chlorine atom, or a bromine atom. p represents an integer of 0 to 2, and is preferably 0 or 1, and more preferably 0. R 12 represents a methyl group or an ethyl group, with a methyl group being preferred. R 13 represents a hydrogen atom or a methyl group, and preferably a hydrogen atom. L represents a divalent linking group, and preferably a group represented by the following general formula (2). General formula (2):-(CO-X 1 )rX 2 - In general formula (2), X 1 is an oxygen atom or NR 30 - where R 30 represents a hydrogen atom, an alkyl group, an aryl group, or an acyl group, each of which may have a substituent (e.g., a halogen atom, a nitro group, or a hydroxyl group). 30 is preferably a hydrogen atom, an alkyl group having 1 to 10 carbon atoms (for example, a methyl group, an ethyl group, an n-butyl group, and an n-octyl group), or an acyl group (for example, an acetyl group and a benzoyl group). 1 is preferably an oxygen atom or NH-. X 2 represents an alkylene group, an arylene group, an alkylenearylene group, an arylenealkylene group, or an alkylenearylenealkylene group, and these groups include -O-, -S-, -CO-, -COO-, -NH-, -SO2-, -N(R 31 )- or -N(R 31 )SO2- etc. may be inserted in the middle. R 31 represents a linear or branched alkyl group having 1 to 6 carbon atoms. 2 is preferably a dimethylene group, a trimethylene group, a tetramethylene group, an o-phenylene group, an m-phenylene group, a p-phenylene group, -CH2CH2OCOCH2CH2-, or -CH2CH2OCO(C6H4)-. r represents 0 or 1. q represents 0 or 1, with 0 being preferred.
[0032] R 14 represents an alkyl group, an alkenyl group, or an alkynyl group, and is preferably an alkyl group having 5 to 50 carbon atoms, more preferably an alkyl group having 5 to 30 carbon atoms, and even more preferably an alkyl group having 5 to 20 carbon atoms. R 15 is a hydrogen atom, a methyl group, an ethyl group, a halogen atom, or -CH2COOR 16 represents a hydrogen atom, a methyl group, a halogen atom, or -CH2COOR 16 is preferred, and a hydrogen atom, a methyl group, or -CH2COOR 16 is more preferred, and a hydrogen atom is even more preferred. R 16 represents a hydrogen atom or an alkyl group having 1 to 80 carbon atoms, and R 14 may be the same as or different from R 16 The number of carbon atoms is preferably 1 to 70, and more preferably 1 to 60.
[0033] In the general formula (1), x, y, z, and w represent the molar ratio of each repeating unit. x is 3 to 60 mol %, preferably 3 to 50 mol %, and more preferably 3 to 40 mol %. y is 30 to 96 mol %, preferably 35 to 95 mol %, and more preferably 40 to 90 mol %. z is 0.5 to 25 mol %, preferably 0.5 to 20 mol %, and more preferably 1 to 20 mol %. w is 0.5 to 40 mol %, preferably 0.5 to 30 mol %. In the general formula (1), it is preferable that x is 3 to 40 mol %, y is 40 to 90 mol %, z is 0.5 to 20 mol %, and w is 0.5 to 10 mol %.
[0034] The polymer represented by the general formula (1) is preferably a polymer represented by the following general formula (2).
[0035] [ka]
[0036] In the general formula (2), x, y, z and w are as defined above.
[0037] The polymer represented by general formula (1) may contain repeating units other than the repeating units represented by the above general formulae (A) to (D). Examples of monomers for forming other repeating units include acrylic acid esters, methacrylic acid esters, vinyl esters, olefins, crotonates, itaconic acid diesters, maleic acid diesters, fumaric acid diesters, acrylamides, unsaturated carboxylic acids, allyl compounds, vinyl ethers, vinyl ketones, vinyl heterocyclic compounds, glycidyl esters, and unsaturated nitriles. These monomers are also described in paragraphs 0010 to 0022 of Japanese Patent No. 3754745. In terms of hydrophobicity, acrylic acid esters or methacrylic acid esters are preferred, and hydroxyalkyl methacrylates or hydroxyalkyl acrylates are more preferred. The polymer represented by general formula (1) preferably contains a repeating unit represented by general formula (E).
[0038] [ka]
[0039] In the above formula, L E represents an alkylene group, preferably an alkylene group having 1 to 10 carbon atoms, more preferably an alkylene group having 2 to 6 carbon atoms, and even more preferably an alkylene group having 2 to 4 carbon atoms.
[0040] As the polymer represented by the general formula (1), a polymer represented by the following general formula (3) is particularly preferred.
[0041] [ka]
[0042] In the above formula, a1, b1, c1, d1, and e1 represent the molar ratio of each repeating unit, where a1 represents 3 to 60 (mol%), b1 represents 30 to 95 (mol%), c1 represents 0.5 to 25 (mol%), d1 represents 0.5 to 40 (mol%), and e1 represents 1 to 10 (mol%). The preferred range of a1 is the same as the preferred range of x described above, the preferred range of b1 is the same as the preferred range of y described above, the preferred range of c1 is the same as the preferred range of z described above, and the preferred range of d1 is the same as the preferred range of w described above. e1 is 1 to 10 mol %, preferably 2 to 9 mol %, and more preferably 2 to 8 mol %.
[0043] The specific polymer can be synthesized by referring to, for example, Japanese Patent No. 3305459 and Japanese Patent No. 3754745. The weight average molecular weight of the specific polymer is not particularly limited, but is preferably from 1,000 to 1,000,000, more preferably from 2,000 to 750,000, and even more preferably from 3,000 to 500,000.
[0044] The conductive thin wires may contain materials other than the above-mentioned materials as needed. Examples of the conductive thin wires include antistatic agents, nucleation accelerators, spectral sensitizing dyes, surfactants, antifogging agents, hardeners, anti-black spot agents, redox compounds, monomethine compounds, and dihydroxybenzenes, as described in paragraphs 0220 to 0241 of JP-A-2009-004348. Furthermore, the conductive thin wires may contain physical development nuclei. The conductive thin wire may also contain a crosslinking agent used to crosslink the specific polymers described above. By containing the crosslinking agent, crosslinking between the specific polymers progresses, and the connection between the metals in the conductive thin wire is maintained.
[0045] <Physical properties of conductive thin wires> The line width Wa of the conductive thin wires 14 is the maximum length of the region of the conductive thin wires 14 where the metallic silver 15 is present in the direction DW perpendicular to the direction DL (see FIG. 1 ) in which the conductive thin wires 14 extend. The line width Wa of the conductive thin wires 14 is preferably 0.1 μm or more and less than 5.0 μm in terms of the balance between conductivity and invisibility. In particular, in terms of invisibility of the conductive thin wires 14, the line width Wa is more preferably 2.5 μm or less, and even more preferably 2.0 μm or less. There is no particular lower limit, but in terms of superior conductivity of the conductive thin wires, it is more preferably 0.5 μm or more, and even more preferably 1.2 μm or more. The line width Wa of the above-mentioned conductive thin wire 14 is obtained by using a scanning electron microscope to select any five points corresponding to the line width of one conductive thin wire and calculating the arithmetic mean value corresponding to the line width of the five points.
[0046] The height T of the conductive thin wires is the maximum length of the region of the conductive thin wires 14 where the metallic silver 15 is present in the direction perpendicular to the surface 12a of the substrate 12. The height T of the conductive thin wires 14 is not particularly limited, but is preferably 0.06 μm or more and less than 7.5 μm, more preferably 0.3 to 3.0 μm, in terms of the balance between conductivity and bendability. The height T of the above-mentioned conductive thin wire 14 is obtained by using a scanning electron microscope to select any five points corresponding to the height of one conductive thin wire and calculating the arithmetic mean value of the parts corresponding to the height of the five points.
[0047] In terms of the conductivity of the conductive thin wires 14 and the resistance to breakage due to the influence of the surface pressure of the roll, the ratio (aspect ratio) of the height T of the conductive thin wires 14 to the line width Wa of the conductive thin wires 14 in the vertical cross section Ac is preferably 0.3 to 2.5, more preferably 0.6 or more and less than 1.5, and even more preferably 0.8 to less than 1.3.
[0048] The line resistance of the conductive thin wire is preferably less than 100 Ω / mm, more preferably less than 80 Ω / mm, and even more preferably less than 60 Ω / mm, from the viewpoint of operability when used as a touch panel. The linear resistance is the resistance measured by the four-probe method divided by the distance between the measurement probes. A more specific method for measuring the linear resistance will be described in the Examples below.
[0049] The thin conductive wires may form a predetermined pattern, that is, the conductive substrate may have a pattern formed by the thin conductive wires. The pattern formed by the conductive thin wires is not particularly limited, and examples thereof include triangles such as equilateral triangles, isosceles triangles, and right-angled triangles; quadrilaterals such as squares, rectangles, rhombuses, parallelograms, and trapezoids; (regular) hexagons and (regular) n-gons such as (regular) octagons; circles, ellipses, stars, and geometric shapes that are combinations of these shapes. Furthermore, the pattern formed by the conductive thin wires is more preferably a mesh-like pattern (mesh pattern).
[0050] FIG. 2 is a plan view showing an example of a mesh pattern formed by conductive thin wires of a conductive substrate according to the present invention. The mesh shape refers to a shape including a plurality of openings (lattice) 18 formed by intersecting thin conductive wires 14B, as shown in Fig. 2. The thin conductive wires 14B have the same configuration as the thin conductive wires 14 described above. In FIG. 2, the opening 18 has a diamond (square) shape, but it may have other shapes. For example, it may have a polygonal shape (e.g., a triangle, a rectangle, a hexagon, or a random polygon). Furthermore, the shape of one side may be a straight line, a curved shape, or an arc shape. When it is an arc shape, for example, two opposing sides may be arc shapes that convex outward, and the other two opposing sides may be arc shapes that convex inward. Furthermore, the shape of each side may be a wavy line shape in which an outwardly convex arc and an inwardly convex arc are connected. Of course, the shape of each side may be a sine curve.
[0051] The length L of one side of opening 18 is not particularly limited, but is preferably 1500 μm or less, more preferably 1300 μm or less, and even more preferably 1000 μm or less. Furthermore, the length L of one side of opening 18 is preferably 5 μm or more, more preferably 30 μm or more, and even more preferably 80 μm or more. When the side length of the opening is within the above-mentioned range, transparency can be maintained at a good level, and when the conductive substrate is attached to the front of a display device, the display can be viewed without any sense of incongruity. In terms of visible light transmittance, the opening ratio of the mesh pattern is preferably 90.00% or more, more preferably 95.00% or more, and even more preferably 99.50% or more. There is no particular upper limit, but it can be less than 100%. The aperture ratio corresponds to the ratio of the area on the substrate excluding the area where the conductive thin wires are located in the mesh pattern area to the entire area.
[0052] [Method of manufacturing conductive substrate] Next, a method for producing the conductive substrate will be described. The method for producing the conductive substrate is not particularly limited as long as it can produce a conductive substrate having the above-described configuration, and examples thereof include a production method having the following steps 1 and 2 in this order. Step 1: Forming a thin wire-shaped metal-containing layer on a substrate Step 2: A step of forming conductive thin wires by performing electroless plating on the metal-containing layer.
[0053] In the above manufacturing method, for example, conductive thin wires containing silver can be formed by performing at least one of step 1a of forming a thin wire-shaped silver-containing layer containing silver as the thin wire-shaped metal-containing layer and step 2a of subjecting the metal-containing layer to electroless silver plating treatment. The procedure for each step will be described in detail below.
[0054] [Process 1] Step 1 is a step of forming a thin wire-shaped metal-containing layer on a substrate, which forms a thin wire-shaped metal-containing layer that is to be plated. The substrate used in this step is as described above.
[0055] Examples of the metal include silver, copper, gold, nickel, and palladium, and silver or copper is preferred, with silver being more preferred. That is, step 1 is preferably step 1a of forming a thin wire-shaped silver-containing layer containing silver as the thin wire-shaped metal-containing layer. The metal may be in the form of particles, in which case the average particle size of the metal particles (preferably silver particles) is preferably 10 to 1000 nm, more preferably 10 to 200 nm, and even more preferably 50 to 150 nm, in terms of equivalent sphere diameter. The shape of the metal particles is not particularly limited, and examples thereof include spherical, cubic, tabular (hexagonal tabular, triangular tabular, quadrangular tabular, etc.), octahedral, and tetradecahedral shapes. The metal content of the thin wire is not particularly limited, and is preferably 3.0 to 20.0 g / m in order to provide a conductive substrate with better conductivity. 2 is preferred.
[0056] The thin wire-shaped metal-containing layer preferably contains a polymer, that is, in the thin wire-shaped metal-containing layer, the polymer preferably serves as a binder and the metal is dispersed in the polymer. The type of polymer is not particularly limited, but a specific polymer is preferred in that it can form a conductive thin wire with superior strength. The specific polymer, including preferred embodiments thereof, is as described above. The content of the polymer in the thin wire-shaped metal-containing layer is not particularly limited, and is preferably 0.005 to 2.0 g / m in order to enhance the effects of the present invention. 2 is preferable, and 0.01 to 1.0 g / m 2 is more preferred.
[0057] The method for forming a thin line-shaped metal-containing layer on a substrate is not particularly limited, and a known method can be used. For example, there are a method of performing exposure and development using silver halide, a method of forming a silver-containing layer on the entire surface of a substrate, and then removing part of the layer using a resist pattern to form a thin line-shaped silver-containing layer, and a method of ejecting a composition containing metal-containing particles and a polymer onto a substrate by a known printing method such as inkjet to form a thin line-shaped metal-containing layer. Among these, the method of exposure and development using silver halide is preferred, since it allows the production of a conductive substrate that exhibits the effects of the present invention more effectively.
[0058] The method of exposure and development using silver halide preferably comprises the following steps: Step A: A step of forming a silver halide-containing photosensitive layer containing silver halide, gelatin, and a specific polymer on a substrate. Step B: A step of exposing the silver halide-containing photosensitive layer and then developing it to form a fine-line silver-containing layer containing metallic silver, gelatin, and a specific polymer. Step C: A step of subjecting the silver-containing layer obtained in step B to a heat treatment. Step D: A step of removing gelatin from the silver-containing layer obtained in Step C to form the above-mentioned thin line-shaped silver-containing layer. The procedure for each step will be described in detail below.
[0059] <Process A> Step A is a step of forming a silver halide-containing photosensitive layer (hereinafter also referred to as "photosensitive layer") containing silver halide, gelatin, and a specific polymer on a substrate. This step produces a substrate with a photosensitive layer that is then subjected to the exposure treatment described below. First, the materials used in step A will be described in detail, and then the procedure for step A will be described in detail.
[0060] (silver halide) The halogen atom contained in the silver halide may be any of chlorine atom, bromine atom, iodine atom, and fluorine atom, or a combination thereof.For example, silver halide mainly composed of silver chloride, silver bromide, or silver iodide is preferred, and silver halide mainly composed of silver chloride or silver bromide is more preferred.In addition, silver chlorobromide, silver iodochlorobromide, or silver iodobromide is also preferably used. Here, for example, "silver halide mainly composed of silver chloride" refers to a silver halide in which the molar fraction of chloride ions in the total halide ions in the silver halide composition is 50% or more. This silver halide mainly composed of silver chloride may contain bromide ions and / or iodide ions in addition to chloride ions.
[0061] The silver halide is usually in the form of solid particles, and the average particle size of the silver halide is preferably from 10 to 1000 nm, more preferably from 10 to 200 nm, and even more preferably from 50 to 150 nm, in terms of equivalent spherical diameter. The shape of the silver halide grains is not particularly limited, and examples thereof include spherical, cubic, tabular (hexagonal tabular, triangular tabular, quadrangular tabular, etc.), octahedral, and tetradecahedral shapes.
[0062] (gelatin) The type of gelatin is not particularly limited, and examples thereof include lime-processed gelatin and acid-processed gelatin. In addition, gelatin hydrolysates, enzymatic decomposition products, and gelatin modified with amino groups and / or carboxyl groups (phthalated gelatin and acetylated gelatin) may also be used.
[0063] (Specific polymer) The photosensitive layer contains a polymer (specific polymer) different from gelatin. By including this specific polymer in the photosensitive layer, the silver-containing layer and the conductive thin wires formed from the photosensitive layer have superior strength. The type, specific examples, shape, and other characteristics of the specific polymer are as described above.
[0064] The photosensitive layer may contain materials other than the above-mentioned materials, if necessary. Examples of the other materials include metal compounds belonging to Groups 8 and 9, such as rhodium compounds and iridium compounds, which are used to stabilize silver halide and increase its sensitivity. Other examples of the other materials include the other materials that may be contained in the conductive thin wires described above. These materials other than gelatin and the specific polymer may be contained in a silver halide-free layer and / or a protective layer, which will be described later.
[0065] (Step A procedure) The method for forming the photosensitive layer containing the above components in step A is not particularly limited, but from the viewpoint of productivity, a method in which a composition for forming a photosensitive layer containing silver halide, gelatin, and a specific polymer is brought into contact with a substrate to form a photosensitive layer on the substrate is preferred.
[0066] (Materials contained in the composition for forming the photosensitive layer) The composition for forming a photosensitive layer contains the above-mentioned silver halide, gelatin, and specific polymer. If necessary, the specific polymer may be contained in the composition for forming a photosensitive layer in the form of particles. The photosensitive layer-forming composition may contain a solvent, if necessary. Examples of the solvent include water, organic solvents (such as alcohols, ketones, amides, sulfoxides, esters, and ethers), ionic liquids, and mixed solvents thereof.
[0067] The method for contacting the photosensitive layer-forming composition with the substrate is not particularly limited, and examples thereof include a method of applying the photosensitive layer-forming composition onto the substrate and a method of immersing the substrate in the photosensitive layer-forming composition. After the above treatment, a drying treatment may be carried out as necessary.
[0068] (Silver halide-containing photosensitive layer) The photosensitive layer formed by the above procedure contains silver halide, gelatin, and a specific polymer. The content of silver halide in the photosensitive layer is not particularly limited, but in order to obtain a more excellent effect of the present invention, it is preferred that the content be 3.0 to 20.0 g / m in terms of silver. 2 is preferred, and 5.0 to 15.0 g / m 2 is more preferred. The term "silver equivalent" means that the silver halide is converted into the mass of silver produced by reduction. The content of the specific polymer in the photosensitive layer is not particularly limited, but is preferably 0.04 to 2.0 g / m in order to obtain a more excellent effect of the present invention. 2 is preferable, and 0.08 to 0.40 g / m 2 is more preferred.
[0069] <Process B> In step B, the photosensitive layer is exposed to light and then developed to form a fine line-shaped silver-containing layer containing metallic silver, gelatin, and a specific polymer.
[0070] By exposing the photosensitive layer to light, a latent image is formed in the exposed areas. The exposure may be carried out in a pattern. For example, in order to obtain a mesh pattern consisting of the above-mentioned conductive thin wires, examples include a method of exposing through a mask having a mesh-shaped opening pattern, and a method of exposing in a mesh pattern by scanning with laser light. The type of light used for exposure is not particularly limited as long as it can form a latent image on the silver halide, and examples thereof include visible light, ultraviolet light, and X-rays.
[0071] When exposing through a mask having an aperture pattern, the amount of exposure may be adjusted by reducing the exposure dose only at specific locations in the mask aperture pattern. Adjusting the amount of latent image formation allows for adjustment of the amount of metal formed and its thickness (height) in subsequent operations. There are no particular limitations on the means for reducing the exposure dose only at specific locations, but examples include adjusting the exposure dose from the light source irradiating the specific location. For example, methods include reducing the output of only the lamp or LED above that location to lower the exposure dose, or installing a neutral density filter above the specific location. Another method for reducing the exposure dose only at specific locations is to use a half-tone mask in which a semi-transparent film is applied to specific locations of the mask aperture pattern. From the perspective of productivity, using a half-tone mask is preferable.
[0072] By subjecting the exposed photosensitive layer to a development process, metallic silver is precipitated in the exposed areas (areas where a latent image is formed). The method of development is not particularly limited, and examples thereof include known methods used for silver halide photographic films, photographic paper, films for printing plate making, and emulsion masks for photomasks. The development process usually uses a developer, and the type of developer is not particularly limited, but examples include PQ (phenidone hydroquinone) developer, MQ (Metol hydroquinone) developer, and MAA (Metol ascorbic acid) developer.
[0073] This step may further include a fixing treatment for the purpose of removing and stabilizing the silver halide in the unexposed areas. Fixing treatment is carried out simultaneously with and / or after development. The method of fixing treatment is not particularly limited, and examples thereof include methods used for silver halide photographic film, photographic paper, film for printing plate making, and emulsion masks for photomasks. In the fixing process, a fixing solution is usually used. The type of fixing solution is not particularly limited, and examples thereof include the fixing solutions described on page 321 of "Chemistry of Photography" (by Sasai, published by Shashin Kogyo Shuppansha Co., Ltd.).
[0074] By carrying out the above treatment, a thin line-shaped silver-containing layer containing metallic silver, gelatin, and a specific polymer is formed. An example of a method for adjusting the line width of the silver-containing layer is to adjust the opening width of a mask used during exposure. In addition, when a mask is used during exposure, the width of the silver-containing layer formed can be adjusted by adjusting the exposure dose. For example, when the opening width of the mask is narrower than the target width of the silver-containing layer, the width of the region where the latent image is formed can be adjusted by increasing the exposure dose more than usual. Furthermore, when a laser beam is used, the exposure area can be adjusted by adjusting the focusing range and / or scanning range of the laser beam.
[0075] <Process C> Step C is a step of subjecting the silver-containing layer obtained in Step B to a heat treatment. By carrying out this step, fusion between specific polymers in the silver-containing layer progresses, and the strength of the silver-containing layer is improved.
[0076] The heat treatment method is not particularly limited, and examples thereof include a method of bringing the silver-containing layer into contact with superheated steam and a method of heating the silver-containing layer with a temperature control device (e.g., a heater), and the method of bringing the silver-containing layer into contact with superheated steam is preferred.
[0077] The superheated steam may be superheated steam or a mixture of superheated steam and other gases. The contact time between the superheated vapor and the silver-containing layer is not particularly limited, and is preferably 10 to 70 seconds. The supply rate of superheated steam is 500 to 600 g / m 3 The temperature of the superheated steam is preferably 100 to 160°C, more preferably 100 to 120°C at 1 atmospheric pressure.
[0078] The heating conditions for the method of heating the silver-containing layer with a temperature controller are preferably 100 to 200° C. (more preferably 100 to 150° C.) for 1 to 240 minutes (more preferably 60 to 150 minutes).
[0079] <Process D> Step D is a step of removing gelatin from the silver-containing layer obtained in Step C to form a thin-line silver-containing layer. By performing this step, the gelatin is removed from the silver-containing layer, and the thin-line silver-containing layer having voids formed therein is formed. A plating solution described later penetrates into these voids, forming a metal plating. When removing the gelatin, all of the gelatin in the silver-containing layer may be removed, or a portion of the gelatin may be removed so as to remain.
[0080] The method for removing gelatin is not particularly limited, and examples thereof include a method using a protease (hereinafter also referred to as "Method 1") and a method for decomposing and removing gelatin using an oxidizing agent (hereinafter also referred to as "Method 2").
[0081] The proteolytic enzyme used in Method 1 includes known plant or animal enzymes that can hydrolyze proteins such as gelatin. Examples of proteolytic enzymes include pepsin, rennin, trypsin, chymotrypsin, cathepsin, papain, ficin, thrombin, renin, collagenase, bromelain, and bacterial proteases, with trypsin, papain, ficin, and bacterial proteases being preferred. The procedure in Method 1 may be any method that brings the silver-containing layer into contact with the protease, such as bringing the silver-containing layer into contact with a treatment liquid containing a protease (hereinafter also referred to as "enzyme liquid"). Examples of contacting methods include immersing the silver-containing layer in the enzyme liquid and applying the enzyme liquid onto the silver-containing layer. The content of the protease in the enzyme solution is not particularly limited, and is preferably 0.05 to 20% by mass, more preferably 0.5 to 10% by mass, relative to the total amount of the enzyme solution, in that the degree of decomposition and removal of gelatin can be easily controlled. The enzyme solution usually contains water in addition to the protease. The enzyme solution may contain other additives (for example, a pH buffer, an antibacterial compound, a humectant, and a preservative) as needed. The pH of the enzyme solution is selected so as to maximize the activity of the enzyme, and generally, a pH of 5 to 9 is preferred. The temperature of the enzyme solution is preferably a temperature at which the activity of the enzyme is enhanced, specifically 20 to 45°C.
[0082] If necessary, after the treatment with the enzyme solution, the resulting silver-containing layer may be washed with warm water. The washing method is not particularly limited, and a method of bringing the silver-containing layer into contact with warm water is preferred. Examples include a method of immersing the silver-containing layer in warm water and a method of applying warm water onto the silver-containing layer. The optimum temperature of the hot water is selected depending on the type of protease used, and is preferably 20 to 80°C, more preferably 40 to 60°C, from the viewpoint of productivity. The contact time (washing time) between the hot water and the silver-containing layer is not particularly limited, and from the viewpoint of productivity, it is preferably 1 to 600 seconds, more preferably 10 to 180 seconds.
[0083] The oxidizing agent used in Method 2 may be any oxidizing agent that can decompose gelatin, and is preferably an oxidizing agent with a standard electrode potential of +1.5 V or higher. The standard electrode potential here refers to the standard electrode potential (25°C, E0) of the oxidizing agent in an aqueous solution relative to a standard hydrogen electrode. Examples of the oxidizing agent include persulfuric acid, percarbonate, perphosphoric acid, hypoperchloric acid, peracetic acid, metachloroperbenzoic acid, hydrogen peroxide, perchloric acid, periodic acid, potassium permanganate, ammonium persulfate, ozone, hypochlorous acid or a salt thereof, etc. Among these, from the viewpoints of productivity and economy, hydrogen peroxide (standard electrode potential: 1.76 V), hypochlorous acid or a salt thereof are preferred, and sodium hypochlorite is more preferred.
[0084] The procedure in Method 2 may be any method that brings the silver-containing layer into contact with the oxidizing agent, such as a method of bringing the silver-containing layer into contact with a treatment liquid containing an oxidizing agent (hereinafter also referred to as "oxidizing agent liquid"). Examples of the contact method include a method of immersing the silver-containing layer in the oxidizing agent liquid and a method of applying the oxidizing agent liquid onto the silver-containing layer. The type of solvent contained in the oxidizing agent liquid is not particularly limited, and examples thereof include water and organic solvents.
[0085] <Process E> Step 1 may include, before step A, step E of forming a silver halide-free layer containing gelatin and a specific polymer on the substrate. By carrying out this step, a silver halide-free layer is formed between the substrate and the silver halide-containing photosensitive layer. This silver halide-free layer plays the role of a so-called antihalation layer and also contributes to improving adhesion between the conductive thin wires and the substrate. The silver halide-free layer contains the above-mentioned gelatin and specific polymer, while the silver halide-free layer does not contain any silver halide. The ratio of the mass of the specific polymer to the mass of gelatin in the silver halide-free layer (mass of specific polymer / mass of gelatin) is not particularly limited, but is preferably 0.1 to 5.0, more preferably 1.0 to 3.0. The content of the specific polymer in the silver halide-free layer is not particularly limited, and is not more than 0.03 g / m 2 In most cases, the adhesiveness of the conductive thin wire is better, so 1.0 g / m 2 The upper limit is not particularly limited, but is preferably 1.63 g / m 2 The following cases are common:
[0086] The method for forming the silver halide-free layer is not particularly limited, and examples thereof include a method in which a layer-forming composition containing gelatin and a specific polymer is applied to a substrate, and if necessary, a heat treatment is carried out. The layer-forming composition may contain a solvent, if necessary. Examples of the solvent include the solvents used in the photosensitive layer-forming composition described above. The thickness of the silver halide-free layer is not particularly limited, and is often 0.05 μm or more. In terms of better adhesion of the conductive thin wires, it is preferably more than 1.0 μm, and more preferably 1.5 μm or more. The upper limit is not particularly limited, but it is preferably less than 3.0 μm.
[0087] <Process F> Step 1 may include step F, which is performed after step A and before step B, of forming a protective layer containing gelatin and a specific polymer on the silver halide-containing photosensitive layer. By providing a protective layer, the scratch resistance and mechanical properties of the photosensitive layer can be improved. The ratio of the mass of the specific polymer to the mass of gelatin in the protective layer (mass of specific polymer / mass of gelatin) is not particularly limited, but is preferably more than 0 and not more than 2.0, more preferably more than 0 and not more than 1.0. The content of the specific polymer in the protective layer is not particularly limited, and is not more than 0 g / m 2 Super 0.3g / m 2 Preferably, 0.005 to 0.1 g / m or less 2 is more preferred.
[0088] The method for forming the protective layer is not particularly limited, and examples thereof include a method in which a protective layer-forming composition containing gelatin and a specific polymer is applied onto a silver halide-containing photosensitive layer, and if necessary, a heat treatment is carried out. The composition for forming a protective layer may contain a solvent, if necessary. Examples of the type of solvent include the solvents used in the composition for forming a photosensitive layer described above. The thickness of the protective layer is not particularly limited, but is preferably 0.03 to 0.3 μm, and more preferably 0.075 to 0.20 μm.
[0089] The above-mentioned steps E, A, and F may be carried out simultaneously by simultaneous multilayer coating.
[0090] [Process G] The method for producing a conductive substrate preferably includes, after step 1 and before step 2, step G, in which the thin wire-shaped metal-containing layer (hereinafter simply referred to as "thin wires") formed on the substrate in step 1 is brought into contact with a solution containing an organic acid. Step G causes the organic acid to adhere to the surface of the thin wires, which inhibits plating deposition on the surface of the thin wires during the plating treatment in step 2 described below, and makes it easier for the plating treatment solution to penetrate into the thin wires. As a result, metal (metal plating) is more likely to deposit inside the thin wires, achieving the desired effect.
[0091] (Solution containing organic acid) The type of organic acid contained in the solution containing an organic acid (hereinafter also simply referred to as "first solution") is not particularly limited, and may be any acid containing a carbon atom, such as carboxylic acid (organic compound having a carboxy group), sulfonic acid (organic compound having a sulfonic acid group), and phosphonic acid (organic compound having a phosphonic acid group). Of these, carboxylic acid is preferred.
[0092] The molecular weight of the organic acid (for example, carboxylic acid) is not particularly limited, but is preferably 60 to 400, and more preferably 90 to 300.
[0093] The carboxylic acid may be a monovalent carboxylic acid or a divalent or higher (polyvalent) carboxylic acid, with polyvalent carboxylic acids being preferred. As the divalent or higher carboxylic acid, divalent to heptavalent carboxylic acids are preferred, and divalent to tetravalent carboxylic acids are more preferred. The above valence indicates the number of carboxy groups contained, and a monovalent carboxylic acid is a compound having one carboxy group. The carboxylic acid may have a polar group other than the carboxy group (for example, a hydroxy group, an amino group, a carbonyl group, or an ether group).
[0094] Examples of carboxylic acids include monocarboxylic acids such as acetic acid, lactic acid, and hydroxybutyric acid; dicarboxylic acids such as oxalic acid, malonic acid, tartaric acid, L-aspartic acid, DL-malic acid, oxaloacetic acid, succinic acid, glutamic acid, 2-oxoglutaric acid, glutaric acid, adipic acid, and pimelic acid; tricarboxylic acids such as citric acid, 1,2,3-propanetricarboxylic acid, and 1,3,5-pentatricarboxylic acid; tetracarboxylic acids such as 1,2,3,4-butanetetracarboxylic acid, ethylenediaminetetraacetic acid, and ethylene glycol bis(β-aminoethyl ether)-N,N,N,N-tetraacetic acid; and pentacarboxylic acids such as diethylenetriaminepentaacetic acid.
[0095] The first solution contains a solvent. The type of solvent is not particularly limited, and examples thereof include water, organic solvents (e.g., alcohols, ketones, amides, sulfoxides, esters, and ethers), ionic liquids, and mixed solvents thereof. Among these, water is preferred.
[0096] The content of the organic acid in the first solution is not particularly limited, but is preferably 0.2 to 5 mass %, more preferably 0.5 to 3 mass %, relative to the total mass of the first solution. The pH value of the first solution is not particularly limited, but is preferably 1.5 to 6.0, more preferably 2.0 to 4.0 at a temperature of 25°C. The pH can be measured using a pH meter with a pH electrode.
[0097] (Step G procedure) The method for bringing the thin wires into contact with the first solution is not particularly limited, and examples thereof include a method of immersing a substrate having the thin wires in the first solution, and a method of applying the first solution onto the thin wires. The contact time between the thin wire and the first solution is not particularly limited, and from the viewpoint of productivity, it is preferably 5 to 180 seconds, more preferably 20 to 120 seconds. The temperature of the first solution when the thin wire is brought into contact with the first solution is not particularly limited, but is preferably 30 to 100°C, more preferably 65 to 95°C. After contacting the thin wire with the first solution, the thin wire may be washed with a solvent (for example, water) if necessary.
[0098] [Process 2] Step 2 is a step of forming conductive thin wires by subjecting the thin wire-shaped metal-containing layer to electroless plating. By carrying out this step, metal is precipitated on the surface and inside of the thin wire-shaped metal-containing layer. In particular, since the thin wire-shaped silver-containing layer obtained by carrying out the above-mentioned steps A to D has spaces formed by removing gelatin, conductive thin wires are formed by filling these spaces with metal.
[0099] The electroless plating treatment carried out in this step is carried out by a known electroless plating technique (chemical reduction plating or displacement plating). Examples of metals used in plating include silver, copper, nickel, and cobalt. Silver or copper is preferred, and silver is more preferred, as they provide better effects of the present invention. That is, as step 2 of performing electroless plating on the metal-containing layer, a step of performing electroless silver plating or electroless copper plating is preferred, and step 2a of performing electroless silver plating is more preferred, in terms of achieving better effects of the present invention.
[0100] <Plating treatment solution> The plating solution used in the electroless plating process (hereinafter simply referred to as "plating solution") includes a plating solution containing a solvent, metal ions, a reducing agent, and potassium iodide.
[0101] The solvent contained in the plating solution is preferably water. The content of the solvent in the plating solution is not particularly limited, but is preferably 60 to 95 mass % and more preferably 80 to 90 mass % relative to the total mass of the plating solution.
[0102] The type of metal ion contained in the plating solution can be appropriately selected depending on the type of metal to be deposited, and examples thereof include silver ions, copper ions, nickel ions, and cobalt ions. Silver ions or copper ions are preferred, and silver ions are more preferred. The metal ions in the plating solution are derived from, for example, a metal salt added to the plating solution. The type of metal salt added to the plating solution is not particularly limited, and known metal salts can be used. The metal salt is preferably a water-soluble metal salt, which means a metal salt that dissolves in water at a concentration of 0.1 mass % or more. As the metal salt, a silver salt or a copper salt is preferred, and a silver salt is more preferred.
[0103] The silver salt may be an inorganic silver salt or an organic silver salt, with the inorganic silver salt being preferred. Inorganic silver salts include, for example, silver nitrate, silver fluoride, silver perchlorate, and silver sulfate. The content of the silver salt in the plating solution is not particularly limited, and is preferably 0.01 to 5.0 mol / L, more preferably 0.05 to 3.0 mol / L, relative to the total amount of the plating solution. The silver salts may be used alone or in combination of two or more. The silver contained in the silver salt ionizes in the plating solution to form silver ions.
[0104] The type of reducing agent contained in the plating solution is not particularly limited, and any known reducing agent can be used. Examples of reducing agents include ascorbic acid compounds or salts thereof, such as ascorbic acid and isoascorbic acid; hydrazines or salts thereof, such as hydrazine, hydrazine monohydrate, hydrazine sulfate, and hydrazine chloride; hydroquinones or derivatives thereof, such as hydroquinone and methylhydroquinone; and pyrogallols or derivatives thereof, such as pyrogallol, pyrogallol monomethyl ether, pyrogallol-4-carboxylic acid, pyrogallol-4,6-dicarboxylic acid, and gallic acid. The content of the reducing agent in the plating solution is not particularly limited, but is preferably 2 mol / L or less, more preferably 0.1 mol / L or less, and even more preferably 0.06 mol / L (60 mmol / L) or less, relative to the total amount of the plating solution. The lower limit is not particularly limited, but is preferably 0.01 mol / L (10 mmol / L) or more, more preferably 0.02 mol / L (20 mmol / L) or more, relative to the total amount of the plating solution. The reducing agent may be used alone or in combination of two or more kinds.
[0105] The plating solution used in the electroless plating process contains potassium iodide. The content of potassium iodide in the plating solution is, for example, preferably 0.001 to 1 mmol / L, more preferably 0.01 to 0.1 mmol / L, relative to the total amount of the plating solution.
[0106] In addition, since it becomes easier to form conductive thin wires when the ratio I / Ag is in the above range, the content of potassium iodide in the plating solution is C KI mmol / L, and the content of the reducing agent in the plating solution is C R When expressed as mmol / L, the ratio C calculated from the following formula (1) is preferably less than 5, more preferably less than 1, even more preferably less than 0.8, and particularly preferably 0.7 or less. There is no particular lower limit to the ratio C, but it is preferably 0.01 or more, more preferably 0.1 or more, and even more preferably 0.3 or more. Ratio C=C KI / C R ×1000 (1)
[0107] In particular, the plating solution used in the electroless plating treatment contains potassium iodide and a reducing agent, and the content of the reducing agent in the plating solution is 60 mmol / L or less relative to the total amount of the plating solution, and the contents of the potassium iodide and the reducing agent in the plating treatment solution are each C KI mmol / L and C R When expressed as mmol / L, the ratio C = C KI / C R A plating solution that satisfies ×1000≦0.7 is preferred. The preferred ranges for the lower limit of the content of the reducing agent, the content of potassium iodide, and the lower limit of the ratio C are as described above. The plating solution used in the electroless plating treatment is preferably adjusted so that the content of potassium iodide and / or the reducing agent falls within the above-mentioned preferred content range.
[0108] The plating solution may contain other components in addition to the above components, such as a stabilizer that improves the stability of silver ions ionized from the silver salt, and a pH adjuster. The pH of the plating solution is not particularly limited, but is preferably alkaline, more preferably 8.5 to 11.0, and even more preferably 9.0 to 10.5 at a temperature of 25° C., in order to achieve better effects of the present invention.
[0109] <Plating process procedure> The procedure for the above-mentioned plating treatment is not particularly limited, and any method can be used as long as it brings the metal-containing layer into contact with a plating solution. Examples of the method include a method of immersing the metal-containing layer in a plating solution and a method of applying a plating solution onto the metal-containing layer. The contact time between the metal-containing layer and the plating solution is not particularly limited, and is preferably 25 seconds to 30 minutes in terms of the superior effect of the present invention and productivity. After contact with the plating solution, the metal-containing layer may be washed with water or neutralized with an acidic solution having a pH of 3 to 7. The pH of the acidic solution used for neutralization washing is preferably 4 to 6. If the pH of the acidic solution is 3 to 7, sulfur and the like are not generated from sulfurous acid derived from the plating solution. Furthermore, an increase in the pH of the plating solution is suppressed, and the plating reaction can be stopped. The acidic solution functions as a plating stop solution. The acidic solution preferably has a buffering effect, and a solids concentration of 0.1% by mass or more is preferred since it exhibits sufficient buffering ability. The temperature of the plating solution is preferably 10 to 40°C, more preferably 15 to 30°C. The contact time is not particularly limited, and is preferably 5 to 60 seconds in terms of the superior effect of the present invention and productivity.
[0110] [Other steps] The method for producing a conductive substrate may include steps other than the above steps 1 and 2.
[0111] <Process 3> The method for producing a conductive substrate may further include step 3 of subjecting the conductive thin wires obtained in the above step to a smoothing treatment. By carrying out this step, a conductive thin wire having superior conductivity can be obtained.
[0112] The method of smoothing treatment is not particularly limited, and for example, a calendering treatment step in which the substrate having the conductive thin wires is passed between at least a pair of rolls under pressure is preferred. Hereinafter, the smoothing treatment using calender rolls will be referred to as calendering treatment. The rolls used for the calendering treatment include plastic rolls and metal rolls, with plastic rolls being preferred from the viewpoint of preventing wrinkles. The pressure between the rolls is not particularly limited, but is preferably 2 MPa or more, more preferably 4 MPa or more. The pressure between the rolls is preferably 120 MPa or less. The pressure between the rolls can be measured using a Prescale (for high pressure) manufactured by Fujifilm Corporation. The temperature for the smoothing treatment is not particularly limited, but is preferably 10 to 100°C, and more preferably 10 to 50°C.
[0113] <Step 4> The method for producing a conductive substrate may include step 3 of subjecting the conductive thin wire obtained in the above step to a heat treatment. By carrying out this step, conductive thin wires with superior conductivity can be obtained. The heat treatment carried out in step 3 may be the heat treatment carried out in step C described above.
[0114] [Application] The conductive substrate according to the present invention can be used in a variety of applications, including touch panels (or touch panel sensors), semiconductor chips, various electric wiring boards, FPCs (Flexible Printed Circuits), COFs (Chip on Film), TABs (Tape Automated Bonding), antennas, multilayer wiring boards, and motherboards. In particular, the conductive substrate according to the present invention is preferably used for touch panels (capacitive touch panels). When the conductive substrate of the present invention is used in a touch panel, the conductive thin wires can effectively function as detection electrodes. When the conductive substrate of the present invention is used in a touch panel, examples of the display panel that can be used in combination with the conductive substrate include a liquid crystal panel and an OLED (Organic Light Emitting Diode) panel, and a combination with an OLED panel is preferred.
[0115] The conductive substrate may have, in addition to the conductive thin wires, a conductive part having a different configuration from the conductive thin wires. This conductive part may be electrically connected to the conductive thin wires to establish conduction. Examples of the conductive part include peripheral wiring that applies a voltage to the conductive thin wires, and alignment marks that adjust the position of the conductive substrate and the members to be laminated thereon.
[0116] Other uses of the conductive substrate of the present invention include, for example, an electromagnetic wave shield that blocks electromagnetic waves such as radio waves and microwaves (ultra-high frequency waves) generated from electronic devices such as personal computers and workstations, and prevents static electricity. Such an electromagnetic wave shield can be used not only in personal computers, but also in electronic devices such as video recording devices and electronic medical devices. The conductive substrate of the present invention can also be used in a transparent heating element.
[0117] The conductive substrate of the present invention may be used in the form of a laminate comprising the conductive substrate and other members such as a pressure-sensitive adhesive sheet and a release sheet during handling and transportation. The release sheet functions as a protective sheet to prevent scratches on the conductive substrate during transportation of the laminate. The conductive substrate may also be handled in the form of a composite having, for example, a conductive substrate, an adhesive sheet, and a protective layer in this order.
[0118] The present invention is basically configured as described above. Although the conductive substrate of the present invention has been described in detail, the present invention is not limited to the above-described embodiment, and various improvements or modifications may be made without departing from the spirit and scope of the present invention. [Example]
[0119] The features of the present invention will be explained in more detail below with reference to examples. The materials, reagents, amounts and proportions of substances, and procedures shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the following examples.
[0120] [Example 1] (Preparation of Silver Halide Emulsion) To the following solution 1, maintained at 30°C and pH 4.5, 90% of each of the following solutions 2 and 3 were added simultaneously over 20 minutes while stirring the solution 1, forming 0.16 μm core particles. Next, the following solutions 4 and 5 were added to the resulting solution over 8 minutes, and then the remaining 10% of the following solutions 2 and 3 were added over 2 minutes, growing the core particles to 0.10 μm. Furthermore, 0.15 g of potassium iodide was added to the resulting solution, and the solution was aged for 5 minutes to complete grain formation.
[0121] 1 liquid: 750ml water 8.6g gelatin 3g potassium bromide 1,3-dimethylimidazolidine-2-thione 20mg Sodium benzenethiosulfonate 10mg Citric acid 0.7g 2 liquid: 300ml water Silver nitrate 150g 3 liquid: 300ml water 38g sodium chloride 32g potassium bromide Potassium hexachloroiridate(III) (0.005%KCl 20% aqueous solution) 5ml Ammonium hexachlororhodate (0.001%NaCl 20% aqueous solution) 7ml 4 liquid: 100ml water Silver nitrate 50g 5 liquid: 100ml water Sodium chloride 13g Potassium bromide 11g Yellow prussic acid 5mg
[0122] The emulsion was then washed by the usual flocculation method. Specifically, the temperature of the resulting solution was lowered to 35°C, and the pH was lowered using sulfuric acid until the silver halide precipitated (pH 3.6 ± 0.2). Approximately 3 L of the supernatant was removed from the resulting solution (first wash). 3 L of distilled water was then added to the resulting solution, and sulfuric acid was added until the silver halide precipitated. Another 3 L of the supernatant was removed from the resulting solution (second wash). The same procedure as the second wash was repeated once more (third wash), completing the washing and desalting steps. The emulsion after washing and desalting was adjusted to pH 6.4 and pAg 7.5, and chemically sensitized to obtain the optimum sensitivity by adding 2.5 g of gelatin, 10 mg of sodium benzenethiosulfonate, 3 mg of sodium benzenethiosulfinate, 15 mg of sodium thiosulfate, and 10 mg of chloroauric acid at 55°C. Then, 100 mg of 1,3,3a,7-tetraazaindene as a stabilizer and 100 mg of Proxel (trade name, manufactured by ICI Co., Ltd.) as a preservative were added to the resulting emulsion. The finally obtained emulsion was a silver chlorobromide cubic grain emulsion containing 0.08 mol % of silver iodide and a silver chlorobromide ratio of 70 mol % of silver chloride and 30 mol % of silver bromide, with an average grain size (equivalent to a sphere) of 100 nm and a coefficient of variation of 9%.
[0123] (Preparation of Photosensitive Layer Forming Composition) The above emulsion was treated with 1,3,3a,7-tetraazaindene (1.2 × 10 -4 mol / mol Ag), hydroquinone (1.2 × 10 -2 mol / mol Ag), citric acid (3.0 × 10 -4 The composition was then adjusted to a pH of 5.6 with citric acid. To the above composition, a polymer latex containing a polymer represented by the following formula (P-1) (hereinafter also referred to as "Polymer 1"), a dispersant consisting of dialkylphenyl PEO (PEO is an abbreviation for polyethylene oxide) sulfate ester, and water (the ratio of the mass of dispersant to the mass of Polymer 1 (mass of dispersant / mass of Polymer 1, unit: g / g) was 0.02, and the solid content was 22% by mass) was added so that the ratio of the mass of Polymer 1 to the total mass of gelatin in the composition (mass of Polymer 1 / mass of gelatin, unit: g / g) was 0.25 / 1, thereby obtaining a polymer latex-containing composition. Here, in the polymer latex-containing composition, the ratio of the mass of gelatin to the mass of silver derived from silver halide (mass of gelatin / mass of silver derived from silver halide, unit: g / g) was 0.11. Furthermore, EPOXY RESIN DY 022 (trade name: manufactured by Nagase ChemteX Corporation) was added as a crosslinking agent. The amount of the crosslinking agent added was determined so that the amount of the crosslinking agent in the silver halide-containing photosensitive layer described below was 0.09 g / m 2 Furthermore, surfactant 1, surfactant 2, and sodium polystyrene sulfonate (molecular weight: approximately 1,000,000) as a thickener were added. In this manner, a composition for forming a photosensitive layer was prepared. Polymer 1 was synthesized with reference to Japanese Patent Nos. 3305459 and 3754745.
[0124] [ka]
[0125] The above-mentioned polymer latex was applied to a 40 μm thick polyethylene terephthalate film ("Fujifilm Corporation rolled long film") to form a 0.05 μm thick primer layer. This process was carried out by roll-to-roll, and the following processes (steps) were also carried out by roll-to-roll in the same manner. The roll width was 1 m and the length was 1000 m.
[0126] (Process E-1, Process A-1, Process F-1) Next, a composition for forming a silver halide-free layer, the above-mentioned composition for forming a photosensitive layer, and the composition for forming a protective layer described below were simultaneously coated in multiple layers on the undercoat layer to form a silver halide-free layer, a silver halide-containing photosensitive layer, and a protective layer on the undercoat layer. Here, the composition for forming the silver halide-free layer comprises the above-mentioned polymer 1, gelatin, a solid dispersion of a dye described below, surfactant 1, surfactant 2, surfactant 3, and an aqueous solution containing sodium polystyrene sulfonate (molecular weight: approximately 1,000,000) as a thickener, and the thickness of the silver halide-free layer is 2.0 μm. The mixture mass ratio of polymer 1 to gelatin in the silver halide-free layer (polymer 1 / gelatin) is 2 / 1, and the content of polymer 1 is 1.3 g / m 2 The dye content was 0.08 g / m 2 The contents of surfactant 1, surfactant 2, surfactant 3, and thickener were each 0.02 g / m 2 , 0.02g / m 2 , 0.02g / m 2 , 0.04g / m 2 It was. The thickness of the silver halide-containing photosensitive layer was 2.5 μm, the mixture mass ratio of polymer 1 to gelatin in the silver halide-containing photosensitive layer (polymer 1 / gelatin) was 0.25 / 1, and the content of polymer 1 was 0.19 g / m 2 The contents of surfactant 1, surfactant 2, and thickener were each 0.04 g / m 2 , 0.01g / m 2 , 0.01g / m 2 It was.
[0127] The protective layer-forming composition was an aqueous solution containing the above-mentioned polymer 1, gelatin, colloidal silica (average particle size 12 nm: Snowtex C, manufactured by Nissan Chemical Industries, Ltd.), surfactant 1, surfactant 2, surfactant 3, surfactant 4, sodium polystyrene sulfonate (molecular weight approximately 1 million) as a thickener, and N,N'-bis(vinylsulfonylacetyl)ethylenediamineethylenebis(vinylsulfonylacetamide) as a gelatin crosslinker, and the protective layer had a thickness of 0.15 μm, a mixing mass ratio of polymer 1 to gelatin in the protective layer (polymer 1 / gelatin) of 0.1 / 1, and a content of polymer 1 of 0.015 g / m 2 The colloidal silica content was 0.1 g / m 2 The contents of surfactant 1, surfactant 2 (average molecular weight 1368), surfactant 3, surfactant 4, and thickener were each 0.01 g / m 2 , 0.02g / m 2 , 0.02g / m 2 , 0.001g / m 2 , 0.01g / m 2 The content of the gelatin crosslinking agent was 3% by mass relative to the total mass of the gelatin in all layers.
[0128] [ka]
[0129] [ka]
[0130] [ka]
[0131] [ka]
[0132] [ka]
[0133] (Process B-1) The photosensitive layer thus prepared was exposed to parallel light from a high-pressure mercury lamp through a lattice-shaped photomask. The photomask used was a pattern-forming mask, and the line width of the unit square lattice forming the lattice shown in Figure 2 was 1.2 μm, and the length L of one side of the lattice (opening) was 600 μm. After exposure, the resulting sample was developed with a developer described below, and then further developed with a fixer (product name: N3X-R for CN16X: manufactured by Fujifilm Corporation), rinsed with pure water at 25°C, and then dried to obtain Sample A, which had a silver-containing layer containing metallic silver formed in a mesh pattern. In Sample A, a conductive mesh pattern area measuring 21.0 cm × 29.7 cm was formed.
[0134] (Developer composition) The following compounds are contained in 1 liter (L) of developer: Hydroquinone 0.037 mol / L N-methylaminophenol 0.016 mol / L Sodium metaborate 0.140 mol / L Sodium hydroxide 0.360 mol / L Sodium bromide 0.031 mol / L Potassium metabisulfite 0.187 mol / L
[0135] The obtained sample A was immersed in warm water at 50° C. for 180 seconds, after which the water was removed with an air shower and the sample was allowed to dry naturally.
[0136] (Process C-1) Sample A obtained in step B-1 was placed in a superheated steam treatment tank at 110°C and left to stand for 30 seconds to undergo superheated steam treatment. The steam flow rate at this time was 100 kg / h.
[0137] (Process D-1) Sample A obtained in step C-1 was immersed in an aqueous protease solution (40°C) for 30 seconds. Sample A was removed from the aqueous protease solution and washed by immersing it in warm water (liquid temperature: 50°C) for 120 seconds. Thereafter, the water was removed with an air shower and the sample was allowed to dry naturally. The aqueous protease solution used was prepared according to the following procedure. Triethanolamine and sulfuric acid were added to an aqueous solution of a protease (Biophrase 30L, manufactured by Nagase ChemteX Corporation) (protease concentration: 0.5% by mass) to adjust the pH to 8.5.
[0138] (Process G-1) Sample A obtained in step D-1 was immersed in a 1% by mass aqueous solution of glutaric acid (70°C) for 2 minutes. Sample A was removed from the aqueous solution of glutaric acid and then immersed in water at 30°C for 5 seconds to be washed. Glutaric acid manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. was used.
[0139] (Process 2-1) Sample A obtained in step G-1 was immersed in plating solution A (30°C) having the following composition for 5 minutes. Sample A was removed from plating solution A and washed by immersing it in a 1% by mass citrate buffer solution (pH = 5, solution temperature: 25°C) for 30 seconds. In other words, neutralization washing was performed. The composition of plating solution A (total volume 1200 ml) was as follows. The pH of plating solution A was 9.9, which was adjusted by adding a specified amount of potassium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.). All of the following components used were manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. No change in line width was observed before and after plating.
[0140] (Composition of plating solution A) 1g AgNO32 86g sodium sulfite Sodium thiosulfate pentahydrate 60g Aron T-50 (manufactured by Toagosei Co., Ltd., solid content 40%) 36g Methylhydroquinone (reducing agent) 6.6g Potassium iodide 0.004g Potassium carbonate (prescribed amount) ·Water remainder
[0141] (Step 4-1) Sample A obtained in step 2-1 was placed in a superheated steam treatment tank at 110°C and left to stand for 30 seconds to undergo superheated steam treatment. The steam flow rate at this time was 100 kg / h.
[0142] In Sample A obtained by step 4-1, the conductive thin wires formed a mesh pattern. The conductive thin wires had a line width of 1.8 μm and a height of 1.8 μm.
[0143] In addition, 100 samples B were produced in which a comb-like pattern for migration testing was formed on a substrate according to the same procedure as above, except that the photomask used in the above (Step B-1) was changed. The pattern for migration testing was a pattern conforming to IPC-TM650 or SM840, with a line width of 10 μm, a space width of 10 μm, a line length of 30 cm, and 17 / 18 lines.
[0144] [Examples 2 to 3, Comparative Examples 1 to 4] In Examples 2 to 3 and Comparative Examples 1 to 4, Sample A having a mesh pattern formed from conductive thin wires and Sample B having a comb-like pattern formed from conductive thin wires were produced according to the procedure described in Example 1, except that instead of Plating Solution A used in Step 2-1 above, plating solutions were used in which the amounts of potassium iodide and methylhydroquinone (reducing agent) added were adjusted so that the contents were as shown in Table 1. All of the components of the immersion solutions used were manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.
[0145] [Measurement of the I / Ag ratio] For the conductive substrates obtained in each of the examples and comparative examples, the ratio I / Ag on the surface of the conductive thin wires was measured according to the method using the fluorescent X-ray analysis described above. The measurement results of the ratio I / Ag are shown in Table 1 below.
[0146] [evaluation] The evaluation methods for the conductivity and migration suppression performance, which are evaluation items for the conductive substrate, will be described below.
[0147] <Conductivity test> The linear resistance value of the conductive mesh pattern region was measured for the obtained conductive substrate sample A. The linear resistance value was obtained by dividing the resistance value measured by the four-probe method by the distance between the measurement terminals. The method for measuring the linear resistance is specifically described below. First, both ends of any one conductive thin wire constituting the mesh pattern of Sample A were broken to separate it from the mesh pattern. Four microprobes (A, B, C, and D) (tungsten probes (diameter: 0.5 μm) manufactured by Micro Support Co., Ltd.) were then brought into contact with the separated conductive thin wire. A constant current I was applied to the outermost probes A and D using a source meter (KEITHLEY Source Meter, 2400-type general-purpose source meter) so that the voltage V between the inner probes B and C, spaced 250 μm apart, was 5 mV, and the resistance Ri = V / I was measured. The measured value was calculated by dividing the obtained resistance Ri by the distance between B and C, and the arithmetic mean of the measured values at any 10 locations was taken as the linear resistance. The conductivity of each Sample A was evaluated from the obtained linear resistance according to the following criteria. Of the following 1 to 5, a rating of 3 or higher is preferable, 4 or higher is more preferable, and 5 is even more preferable. 5: The wire resistance is less than 50 Ω / mm. 4: The wire resistance is 50 Ω / mm or more and less than 60 Ω / mm. 3: The wire resistance is 60 Ω / mm or more and less than 80 Ω / mm. 2: The wire resistance is 80 Ω / mm or more and less than 100 Ω / mm. 1: The wire resistance is 100 Ω / mm or more.
[0148] <Migration test> Sample B was left standing in a humid and hot atmosphere at 60°C and 90% RH, wiring was connected to both ends of Sample B, and a DC current of 5 V was continuously applied to one side. After a certain period of time had passed, Sample B was taken out of the 60°C and 90% RH atmosphere, and the insulation resistance of Sample B was measured using an R8340A manufactured by Advantest Corporation. Based on the elapsed time from the start of the test and the measured value of the insulation resistance of Sample B, the migration suppression performance of Sample B was evaluated according to the following criteria.
[0149] (Migration test evaluation criteria) "A": Insulation resistance remains below 10 even after 500 hours have passed since the start of the test. 10 It was above Ω. "B": The insulation resistance remains below 10 even after 240 hours have passed since the start of the test. 10 Ω or more, but the insulation resistance value was 10 10 It dropped to less than Ω. "C": The insulation resistance value is 10 within 240 hours after the start of the test. 10 It dropped to less than Ω.
[0150] In the table, "C" of "Plating treatment solution" KI The "[mmol / L]" column indicates the content of potassium iodine in the plating solution (unit: mmol / L), and the "C R The "[mmol / L]" column indicates the content of the reducing agent in the plating solution (unit: mmol / L). The "Ratio C" column of "Plating Solution" indicates the content of potassium iodide in the plating solution. KI mmol / L, and the content of the reducing agent in the plating solution is C R When expressed as mmol / L, the ratio C = C KI / C R The value calculated using the formula × 1000 is shown. The "Width [μm]" column of the "Conductive thin wire" indicates the width (unit: μm) of the conductive thin wire, and the "Height [μm]" column indicates the height (unit: μm) of the conductive thin wire. The "I / Ag" column for "Conductive Thin Wire" indicates the ratio of the amount of iodine atoms to the amount of silver atoms on the surface of the conductive thin wire as measured by X-ray fluorescence analysis.
[0151] [Table 1]
[0152] As shown in Table 1 above, the conductive substrate of the present invention exhibited certain effects. [Explanation of symbols]
[0153] 10 Conductive substrate 12 PCB 12a surface 14,14B Conductive thin wire 18 Opening Ac vertical section DL,DW direction L length
Claims
1. A conductive substrate including a substrate and a conductive thin wire including silver disposed on the substrate, The conductive substrate, wherein the ratio of the amount of iodine atoms to the amount of silver atoms detected when the surface of the conductive thin wire is measured by fluorescent X-ray analysis is 0.035 to 0.
100.
2. The conductive substrate according to claim 1 , wherein the conductive thin wires have a line width of 0.1 μm or more and less than 5.0 μm.
3. In a vertical cross section of the conductive thin wire in a direction perpendicular to the direction in which the conductive thin wire extends, 3. The conductive substrate according to claim 1, wherein a ratio of the height of the conductive thin wire to the line width of the conductive thin wire is 0.6 or more and less than 1.
5.
4. The conductive substrate according to claim 1 , wherein the silver contained in the conductive thin wires is in the form of particles.
5. The conductive substrate according to claim 1 or 2, wherein the substrate is a flexible substrate.
6. 6. The conductive substrate according to claim 5, wherein the material constituting the flexible substrate is at least one selected from the group consisting of polyethylene terephthalate, cycloolefin polymer, cycloolefin copolymer, and polycarbonate.
7. A method for producing a conductive substrate, comprising: producing a conductive substrate including a substrate and a conductive thin wire containing silver arranged on the substrate, the method comprising the steps of: A step 1 of forming a thin-line metal-containing layer on the substrate; and step 2 of forming the conductive thin wires by subjecting the metal-containing layer to an electroless plating process, The plating solution used in the electroless plating process contains potassium iodide and a reducing agent, The content of the reducing agent in the plating treatment solution is 60 mmol / L or less, The contents of the potassium iodide and the reducing agent in the plating solution are C KI mmol / L and C R In mmol / L, C KI / C R A method for producing a conductive substrate, which satisfies x 1000≦0.
7.
8. The method for producing a conductive substrate according to claim 7 , wherein the electroless plating treatment is an electroless silver plating treatment.
Citation Information
Patent Citations
Manufacturing method for conductive substrate and conductive substrate
JP2022161790A